The role of lakes for carbon cycling in boreal catchments - Rantakari, Miitta (Finnish Environment Institute, 2013)
Lakes are an important component of ecosystem carbon cycle through both organic carbon sequestration and carbon dioxide and methane emissions, although they cover only a small fraction of the Earth’s surface area. Lake sediments are considered to be one of the rather permanent sinks of carbon in boreal regions and furthermore, freshwater ecosystems process large amounts of carbon originating from terrestrial sources. These carbon fluxes are highly uncertain especially in the changing climate.The present study provides a large-scale view on carbon sources and fluxes in boreal lakes situated in different landscapes. We present carbon concentrations in water, pools in lake sediments, and carbon gas (CO2 and CH4) fluxes from lakes. The study is based on spatially extensive and randomly selected Nordic Lake Survey (NLS) database with 874 lakes. The large database allows the identification of the various factors (lake size, climate, and catchment land use) determining lake water carbon concentrations, pools and gas fluxes in different types of lakes along a latitudinal gradient from 60oN to 69oN.Lakes in different landscapes vary in their carbon quantity and quality. Carbon (C) content (total organic and inorganic carbon) in lakes is highest in agriculture and peatland dominated areas. In peatland rich areas organic carbon dominated in lakes but in agricultural areas both organic and inorganic C concentrations were high. Total inorganic carbon in the lake water was strongly dependent on the bedrock and soil quality in the catchment, especially in areas where human influence in the catchment is low. In inhabited areas both agriculture and habitation in the catchment increase lake TIC concentrations, since in the disturbed soils both weathering and leaching are presumably more efficient than in pristine areas.TOC concentrations in lakes were related to either catchment sources, mainly peatlands, or to retention in the upper watercourses. Retention as a regulator of the TOC concentrations dominated in southern Finland, ...